Current Concept of Bruxism and its Treatment Options - Abhilash Mohapatra1, Gopal Krishna Choudhury2, Sangram Panda3, Upsana Dhar4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
In our day to day clinical practice we come across a lot of patients suffering from occlusal parafunctionalhabits or bruxism. Bruxism can be described as nonfunctional abnormal, involuntary contact of teeth, ifignored it leads to occlusal trauma. So for correct diagnosis and treatment a multidisciplinary approach wasrequired in which dentists, psychiatrists, neurologists and physiotherapists play an important role. Causesfor bruxism were multifactorial and the treatment modalities were also various. Bruxism can be a majorconcern for the dentist as they were required to not only diagnose but also intervene in most of the cases ofbruxism. And if untreated it leads to destruction of dentition, muscle fatigue & temporomandibular pain.This article discusses the history of the current concepts in the diagnosis and treatment of bruxism.